Out of sight, out of mind: Divestments and the global reallocation of pollutive assets - Tobias Berg; Lin Ma; Daniel Streitz (Leibniz Institute for Financial Research SAFE, 2024)
We analyze firms' carbon reduction strategies worldwide and identify one key channel: large, primarily European firms facing increased investor pressure divest pollutive assets to firms that are less in the limelight. There is no evidence of increased engagement in other emission reduction activities. We estimate that 369 million metric tons (mt) of CO2e are reallocated via divestments in the post-Paris Agreement period, shifting pollutive assets from Europe to the rest of the world. Our results indicate significant global asset reallocation effects and imply that responsible investors who want to truly invest responsibly need to monitor firms' divestment strategies closely.
Keywords: G15; G23; G30; G38; M14; Q54; 330; GHG Emissions; Asset Sales; Paris Agreement; Institutional Investors; Investor Pressure; Carbon Disclosure Project